International environmental justice - Яцишин, Роман Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article discusses the features of international environmental justice, analysis of organizational and legalframework for its implementation. In the study author also discusses and outlines options for reform andoutlines the basic directions to perfection of the international judicial system.